Audit Sistem Informasi Jurnal Menggunakan Framework COBIT 5 pada Domain DSS01 dan DSS05 - Ardian Pramana Putra; Jenius Lukman Wibowo; Rizki Ikhwansyah Purba; Sandi Susilo (LKP KARYA PRIMA KURSUS, 2024)
The audit of the journal information system at State Islamic University of North Sumatra in Medan using the COBIT 5 framework was conducted to identify weaknesses and risks in IT governance. The problem faced is the management of operations and security services that have not yet reached the expected capability level. The purpose of this study is to evaluate the journal information system and provide improvement recommendations. The research methodology includes problem identification, literature review, data collection through observation, interviews, and questionnaires, selection of COBIT domains DSS01 and DSS05, data processing, gap analysis, and formulation of improvement recommendations. The audit results show a gap between the current and expected conditions. Improvement recommendations include standardizing operational procedures, training IT staff, implementing continuous monitoring, and using the latest security software. These improvements are expected to enhance the effectiveness and efficiency of the journal information system services at State Islamic University of North Sumatra in Medan.